Investigation of Coastal Environment Change Using Wave Measurement Sensors and Geographical Laser Scanner. (2nd May 2019) - Kim, Kyu-Han; Shin, Bum-Shick; Shim, Kyu-Tae
Abstract : The construction of large-scale coastal structures in any coastal area may not only have direct effects on the coastal environment in that vicinity but also cause severe property damage. In order to prevent this problem, probable effects should be appreciated before any construction and the mechanism that may cause any probable damage must be accurately analyzed along with the plans to minimize damage. This study sought to analyze the cause and mechanism of damage inflicted on coasts by artificial structures through reviewing beach erosions that have occurred on beaches on the east coast of Korea after the large-scale construction of artificial structures, for which wave heights were measured in the vicinity of those structures, and the correlation between the measurements and the analysis data of waves and coastal erosion on the surrounding beach was analyzed. In addition, the correlation between coastal erosion and wave data was applied in order to understand what impact large waves have in relation to sand loss. Accordingly, a movable-bed physical model test was employed to appraise the factors that cause coastal erosion to take place.